2022
DOI: 10.3389/fmicb.2022.909980
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Variation of the Atmospheric Bacterial Community in the Greenlandic High Arctic Is Influenced by Weather Events and Local and Distant Sources

Abstract: The Arctic is a hot spot for climate change with potentially large consequences on a global scale. Aerosols, including bioaerosols, are important players in regulating the heat balance through direct interaction with sunlight and indirectly, through inducing cloud formation. Airborne bacteria are the major bioaerosols with some species producing the most potent ice nucleating compounds known, which are implicated in the formation of ice in clouds. Little is known about the numbers and dynamics of airborne bact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 74 publications
(118 reference statements)
0
7
0
Order By: Relevance
“…Primary biological aerosol particles (PBAP) such as bacteria, spores, pollen, plant debris, or viruses 17 are emitted from vegetation and biological activity on snow and barren land alongside co-emission with sea spray and dust 18 , 19 . PBAP are poorly understood, given the challenges in sampling and quantifying their presence, emissions and sources 20 , especially in the Arctic, where observations are scarce and concentrations are deemed low 21 , 22 . PBAP found in the Arctic can be of both marine (e.g., sea spray and sea ice) and terrestrial origin (e.g., soil and tundra vegetation), locally sourced or transported to the Arctic from lower latitudes 21 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Primary biological aerosol particles (PBAP) such as bacteria, spores, pollen, plant debris, or viruses 17 are emitted from vegetation and biological activity on snow and barren land alongside co-emission with sea spray and dust 18 , 19 . PBAP are poorly understood, given the challenges in sampling and quantifying their presence, emissions and sources 20 , especially in the Arctic, where observations are scarce and concentrations are deemed low 21 , 22 . PBAP found in the Arctic can be of both marine (e.g., sea spray and sea ice) and terrestrial origin (e.g., soil and tundra vegetation), locally sourced or transported to the Arctic from lower latitudes 21 .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported the presence of PBAP in the Arctic 19 , 21 , 23 26 , together with qualitative assessments of their taxonomy 22 , 26 . However, these studies were limited in quantifying PBAP sources due to the limitation with the filter sampling methods used 20 .…”
Section: Introductionmentioning
confidence: 99%
“…Not only that, changes in hydrological conditions, such as soil and runoff inputs [ 29 ], tropical storms, and atmospheric deposition [ 30 ], will also have an impact. Moreover, microbial communities in extreme and simple ecological environments are more susceptible to impacts, and these effects exhibit a clear seasonality [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Snow is an effective scavenger of atmospheric particles, including microorganisms. While previous research has suggested that snow might be used to investigate microbial communities in the atmosphere [ 29 ], their respective community structure and diversity are different [ 30 ]. Selective processes occur as snow falls in the atmosphere [ 17 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…This may be the case for the examples used to test the method such as for microbiomes of tropical trees and the human gut [ 44 ]. The advantage of the seasonal snowpack ecosystem is that freshly fallen snow is the main seeding source, because it consists of both microorganisms in clouds (where snowflakes form) and those scavenged from the underlying air during snowfall [ 30 ]. The surface upon which the seasonal snow develops might also constitute a seeding source, in seasonal snow found on glaciers; this would either be ice or previously fallen snow or firn (aged snow older than a year).…”
Section: Introductionmentioning
confidence: 99%